2011
DOI: 10.1111/j.1600-0625.2011.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct SPINK5 and IL-31 polymorphisms are associated with atopic eczema and non-atopic hand dermatitis in Taiwanese nursing population

Abstract: The term 'hand dermatitis' describes inflammatory skin condition localized to the hands. Nurses working at hospital settings are prone to develop hand dermatitis. The current study aimed to evaluate whether certain genetic polymorphisms were associated with the development of atopic eczema or non-atopic hand dermatitis in Taiwanese population. Nurses of Kaohsiung Medical University Hospital were recruited. Atopic eczema, non-atopic hand dermatitis and normal control groups were identified. The serine protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 42 publications
0
37
0
3
Order By: Relevance
“…IL-31 expression is increased in lesions and serum of patients with AD and correlates with disease severity (30,(33)(34)(35)(36). Furthermore, distinct haplotypes of the IL31 gene are associated with AD (27,37,38).…”
mentioning
confidence: 99%
“…IL-31 expression is increased in lesions and serum of patients with AD and correlates with disease severity (30,(33)(34)(35)(36). Furthermore, distinct haplotypes of the IL31 gene are associated with AD (27,37,38).…”
mentioning
confidence: 99%
“…The similarities in gene expression among Japanese and Taiwanese atopic dermatitis patients may be the reason (Chien et al, 2007;Chang et al, 2012). From genetic studies, the patterns of single nucleotide polymorphism of Taiwanese and Japanese atopic dermatitis patients are much more similar when compared with the Caucasian patients (Chien et al, 2007;Lan et al, 2011). The effects of XFS on gene expression and the feasibility of using XFS among the Caucasian patients are worthy of further studies.…”
Section: Possible Mechanismsmentioning
confidence: 88%
“…[13] Andiappan et al showed no evidence of association of the locus at 5q22.1, even though the effect sizes in the Singaporean Chinese population are similar to that reported in Sun et al [12,14] These results indicate that atopic dermatitis is more multi-factors-involved and complicated disorder than vitiligo and alopecia areata. [15,16] Association of SPINK5 gene polymorphisms with atopic dermatitis has been shown in casecontrol studies, [17][18][19][20] even though genome-wide association studies for atopic dermatisis have not identified the statistic significance. It would be indispensable to accumulate patients with typical atopic dramatis, which should be classified into the extrinsic or intrinsic types, and distinct healthy controls with no family and personal history of atopic dermatitis, allergic rhinitis and/or asthma for next investigation of genome-wide association studies for atopic dermatitis.…”
Section: The Clinical Features Of Netherton Syndromementioning
confidence: 99%